Experimental Study on Kaolinite Weathering Sand as Cement Mortar Accelerating Agent - Wenjuan Wu; Chao Hu; Haifeng Liu; Shijie Ma; Zhenzhong Yuan; Xiaomeng Zhang (Advances in Civil Engineering)
In this study, the weathered sand from kaolinite mine in Yushan County, Jiangxi Province, China, was tested and analyzed in laboratory. XRD results show that montmorillonite is the main mineral composition of kaolinite weathered sand, and the content of montmorillonite is 35%. XRF test results show that the content of aluminum in weathered kaolinite sand is 9.8%. In order to explore the material properties of kaolinite weathered sand as cement mortar accelerating agent, the study compared the quick setting effect of kaolinite weathered sand with an accelerating agent and did the parallel test of 7-day strength of M10 grade mixed mortar. The results show that the 7-day unconfined compressive strength of kaolinite weathered sand fine sand mixed mortar test block is higher than that of accelerating mortar mixed mortar test block when the content of kaolinite weathered fine sand is equal to that of the accelerating agent. However, the 7-day unconfined compressive strength of mortar decreases when the content of fine-grained kaolinite weathered sand increases and the content of cement decreases, indicating that fine-grained kaolinite weathered sand cannot completely replace cement as cement mortar, and the proportion of fine-grained kaolinite weathered sand should be considered according to the strength grade of mixed mortar.